Simulação e projeto de um sistema solar térmico para complemento energético no processo de cura de tabaco - Oliveira, Israel de (Universidade do Vale do Rio dos Sinos, 2014)
Brazil is one of the largest barn tobacco producers and the southern region is largely responsible for this production, especially the state of Rio Grande do Sul. One of the steps involved in this product’s processing chain is the leaves drying (curing), which essentially uses firewood as energy source. This work presents a study of the energy aspects involving the curing of Virginia tobacco, the results and analysis of simulations, using the TRNSYS software, of a solar thermal energy system with water heating to complement this curing process. From the experimental data obtained in curing processes, the most important parameters for the determination of thermal load were defined and the heat losses involved were calculated. The results presented by these simulations showed that the proposed solar energy system, acting as an auxiliary power source of a bulk type barn, can completely meet the thermal load of the first phase of the curing process and contribute to the increase of temperature in the barn necessary to cure this kind of tobacco, reducing 18-39 % the firewood consumption in the process, assuming a seven sunny days period during the summer at the region of Santa Cruz do Sul – RS.
Keywords: Cura; Energia solar térmica; Simulação; TRNSYS; Tabaco; Tobacco; Curing; Solar thermal energy; Simulation; ACCNPQ::Engenharias::Engenharia Mecânica